"Oh, stop! You flatter me": ingratiation in retail settings. Issue 9 (14th September 2015) - Bailey, Ainsworth Anthony
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Even though there has been anecdotal evidence regarding the use of ingratiation techniques in retail salesperson-shopper interactions, surprisingly, there has been limited research on the nature of these ingratiatory techniques and their impact on consumers' perceptions and attitudes. The research reported here was conducted to determine the extent to which different ingratiation techniques that have been identified as techniques used in non-retailing domains are also used by retail salespersons in salesperson-shopper interactions. In addition, it sought to assess whether there are additional ingratiation techniques used by retail salespersons in salesperson-shopper interactions that have not been identified in existing ingratiation literature. The paper aims to discuss these issues. Design/methodology/approach – Two studies, drawing on research on ingratiation in other domains, were conducted in pursuit of realising the purpose. Study 1 was a survey involving a sample of 282 participants, which yielded 267 useable critical incident reports and 283 discrete examples of ingratiatory behaviours. Participants responded to various questions including a critical incident question. Cross-tabulations were, for the main part, used in assessing responses. A second survey involving 158 participants was undertaken as a verification study. This Study 2 yielded 144 useable responses. Findings – Based on a critical incident technique (CIT), other enhancement: compliment and praise was the ingratiation technique most frequently cited by participants in the first sample, with product-customer enhancement being second and favour-rendering third. The Study 2 confirmed other enhancement: compliment and praise and product-customer enhancement as the top two techniques. Four new categories of ingratiatory behaviours emerged in retail salesperson-shopper interactions, and many of the ingratiatory behaviours previously identified in non-retailing contexts also exist in this retailing context. Research limitations/implications – Both samples are US samples, and the method used was the CIT. Though the US samples are appropriate for this study, the study could be extended to other groups and across cultures, to see whether cultural differences in the use of, and consumer responses to, ingratiation techniques exist. The study also did not look at the retail salespeople's perspectives regarding the use of these techniques. Hence further research should address dyadic interpretations of a single ingratiatory encounter; and efforts should also be made to assess how consumers respond to ingratiation in retailing. Practical implications – The studies result in a classification of the influence techniques used most often in retail settings in the USA. Retailers should be aware that customers may, therefore, expect certain kinds of influence tactics and may not respond in the same way when there is a departure from a "customary" influence tactic. Originality/value – Not much research has explored the different kinds of ingratiation techniques used in retail contexts; nor has the stream of research sought to categorise them.